THE EFFECT OF MOTIVATION AND ABILITY ON THE PERFORMANCE OF VILLAGE CADRES AT THE FAMILY PLANNING EXTENSION CENTER IN TANAH PASIR DISTRICT, NORTH ACEH REGENCY - Irfan; Azhari; Ismed Wijaya; Rahmiatul Aula; Isna Hayati; Muhammad Zubaili (CV. Radja Publika, 2025)
This study aims to identify the influence of motivation and ability on the performance of village cadres at the Family Planning Extension Center in Tanah Pasir District, North Aceh Regency. The research method used is a descriptive quantitative method with data collection techniques through interviews and observations, questionnaires and literature studies. Data analysis used in this study uses multiple linear regression. The results of the study show that R or multiple correlations have a value of 0.476 or 47.6%, meaning that the relationship between the independent variables and the dependent variable in this study has a fairly strong relationship. This indicates a positive relationship between motivation and ability on cadre performance. The results of the determination test show that the R Square value is 0.227, meaning that the influence of variables X1 and X2 on Y is 22.7%, while 0.773 is influenced by other factors by 77.3%.